2022
DOI: 10.1186/s12985-022-01851-w
|View full text |Cite
|
Sign up to set email alerts
|

The recombinant Erns and truncated E2-based indirect enzyme-linked immunosorbent assays to distinguishably test specific antibodies against classical swine fever virus and bovine viral diarrhea virus

Abstract: Background Classical swine fever (CSF) virus is the causative agent of an economically important, highly contagious disease of pigs. CSFV is genetically and serologically related to bovine viral diarrhea virus (BVDV). BVDV infection in pigs can mimic CSF clinical signs, which cause difficulty in differentiation. Serological test for detection of virus specific antibodies is a valuable tool for diagnosis and surveillance of CSFV and BVDV infections in animals. The aim of this study was to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In protein manipulation, previous studies have indicated that plant-derived transient expression enhances high protein expression and yield, immunogenicity in animal experiments, and high binding affinity for antibody detection absent in certain conventional expression systems ( Sohn et al, 2018 ; Yamamoto et al, 2018 ; Xu et al, 2022 ). Compared to the transgenic approach for CSFV E2 protein expression using baculovirus ( Wei et al, 2021 ; Bai et al, 2022 ), mammalian cells ( Ji et al, 2018 ; Chen et al, 2023 ), or the E. coli system ( Li et al, 2012 ; Yi et al, 2022 ), the CSFV E2-expressing transgenic plant-derived system was preferable in terms of a large amount and stable expression of the target protein and inexpensiveness, as in recent studies ( Sohn et al, 2018 ; Laughlin et al, 2019 ; Park et al, 2019 , 2020 ; Xu et al, 2022 ). This approach facilitated the purification of recombinant E2 from N. benthamiana extracts.…”
Section: Discussionmentioning
confidence: 99%
“…In protein manipulation, previous studies have indicated that plant-derived transient expression enhances high protein expression and yield, immunogenicity in animal experiments, and high binding affinity for antibody detection absent in certain conventional expression systems ( Sohn et al, 2018 ; Yamamoto et al, 2018 ; Xu et al, 2022 ). Compared to the transgenic approach for CSFV E2 protein expression using baculovirus ( Wei et al, 2021 ; Bai et al, 2022 ), mammalian cells ( Ji et al, 2018 ; Chen et al, 2023 ), or the E. coli system ( Li et al, 2012 ; Yi et al, 2022 ), the CSFV E2-expressing transgenic plant-derived system was preferable in terms of a large amount and stable expression of the target protein and inexpensiveness, as in recent studies ( Sohn et al, 2018 ; Laughlin et al, 2019 ; Park et al, 2019 , 2020 ; Xu et al, 2022 ). This approach facilitated the purification of recombinant E2 from N. benthamiana extracts.…”
Section: Discussionmentioning
confidence: 99%
“…SignalP 4.1 server and TMHMM Serverv.2.0 software analysis showed that BVDV-LC E0 had no signal peptide and transmembrane domain, and BVDV-LC E2 and XJ-04 E2 proteins had no signal peptide, but there were transmembrane regions at 340–362 and 343–365 amino acids, respectively. Some studies have also found that optimizing codon usage preference can enhance the expression and formation of VLPs ( Wang et al, 2020 ; Yi et al, 2022 ). Therefore, the E0 + E2 and E2 + E2 fusion genes were synthesized according to the codon usage preference of insect cells and linked to pMD19-T vector, and then linked to pFastBac1 vector after double enzyme digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we next evaluated the immunogenicity of VLPs in BALB/c mice and their neutralization potential against BVDV NADL strain. VNT is the gold standard for serological diagnosis of BVDV infection, and it is also used as a reference efficacy test for commercial vaccines ( Chimeno et al, 2007 ; Yi et al, 2022 ). The results of VNT showed that the neutralizing antibody levels of mice immunized with vaccines were significantly higher compared with control ( p < 0.0001; 3 and 5 weeks), and even the neutralizing antibody levels of mice immunized with VLPs E0 + E2 or E2 + E2 were significantly higher compared with commercial vaccine ( p < 0.01; 3 or 5 weeks; Figure 3B ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Test results were evaluated using an optical microscope. Titer was read as the highest dilution of serum, resulting in 50% CPE reduction [31]. Sera with neutralizing titers > 1/64 were considered positive.…”
Section: Virus Neutralizing Test (Vnt)mentioning
confidence: 99%